South Asian Peacekeeping: Regional Possibilities. Issue 1 (2nd January 2017) - Basu, Soumita
Abstract: South Asia contributes the largest contingent of peacekeepers to the United Nations, and yet remains a fragile region in terms of peace within its own borders. This article argues that, although the implications of South Asia's engagement in global peacekeeping operations has been the subject of academic study, not enough attention has been paid to how South Asian expertise in peacekeeping can be harnessed as a resource for regional cooperation.